2017
DOI: 10.3329/bjvm.v14i2.31391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Repeat Breeding and Its Effective Treatment in Cows at Selected Areas of Bangladesh

Abstract: ASTRACTThe objectives of the study were to determine the prevalence of repeat breeding and its associated risk factors in cows at selected areas of Bangladesh followed by determination of an effective treatment regime for those cows. Data were collected by interviewing the owner of the cows from 172 farms having 1524 breedable cows located at one Upazila of Mymensingh, Chittagong, Khulna, Satkhira, Bogra and Dhaka districts. A total of 122 repeat breeding cows were treated and randomly distributed into 5 exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 8 publications
3
26
3
Order By: Relevance
“…According to the age, the rate of repeat breeding in ≤3 years,3-4 years and ≥5 years old cows were 19.4,15.3 and 23.5%, respectively in local breed and 10.2,15.3,18.4%, respectively in crossbred cows (Table1).There is no significance (P>0.05) difference of age factors for repeat breeding at less than 3 years but respectively higher responsible more than 5 years. This results is supported by the study of Asaduzzaman et al (2016) who recorded the effects of age of cows on occurrence of repeat breeding significantly lower proportion of cows (29.7 to 33.1%) was affected with repeat breeding at 3-6 years of age than that of 7-13 years of age (37.1 %; P<0.05). It has been widely documented that age impacts negatively on fertility (Hodel et al,1995) and higher repeat breeding rates have been reported in older cows (Hewett,1968).This may be due to variations in hypothalamic or pituitary hormonal levels or different ability of the ovarian response between different age groups (Bullman and Lamming,1978).…”
Section: Effect Of Cow's Entity On Occurrence Of Repeat Breedingsupporting
confidence: 77%
See 2 more Smart Citations
“…According to the age, the rate of repeat breeding in ≤3 years,3-4 years and ≥5 years old cows were 19.4,15.3 and 23.5%, respectively in local breed and 10.2,15.3,18.4%, respectively in crossbred cows (Table1).There is no significance (P>0.05) difference of age factors for repeat breeding at less than 3 years but respectively higher responsible more than 5 years. This results is supported by the study of Asaduzzaman et al (2016) who recorded the effects of age of cows on occurrence of repeat breeding significantly lower proportion of cows (29.7 to 33.1%) was affected with repeat breeding at 3-6 years of age than that of 7-13 years of age (37.1 %; P<0.05). It has been widely documented that age impacts negatively on fertility (Hodel et al,1995) and higher repeat breeding rates have been reported in older cows (Hewett,1968).This may be due to variations in hypothalamic or pituitary hormonal levels or different ability of the ovarian response between different age groups (Bullman and Lamming,1978).…”
Section: Effect Of Cow's Entity On Occurrence Of Repeat Breedingsupporting
confidence: 77%
“…According to BonnevilleHebert et al (2011) from Quebec cows in second, third, and fourth parities had significantly higher odds of being a repeat breeder: in first parity 18%, in second parity 24% and in third parity 42% respectively. Asaduzzaman et al (2016) found significantly (P<0.05) lower proportion of cows (29.1%) was affected with repeat breeding at 2 nd -3 rd parity than that of cows at 1 st parity (33.1%) and 4 th -9 th (47.7%). According to the age, the rate of repeat breeding in ≤3 years,3-4 years and ≥5 years old cows were 19.4,15.3 and 23.5%, respectively in local breed and 10.2,15.3,18.4%, respectively in crossbred cows (Table1).There is no significance (P>0.05) difference of age factors for repeat breeding at less than 3 years but respectively higher responsible more than 5 years.…”
Section: Effect Of Cow's Entity On Occurrence Of Repeat Breedingmentioning
confidence: 89%
See 1 more Smart Citation
“…There are some constraints for achieving these goals. The main limitation of an efficient and profitable reproductive management of the dairy farm is repeat breeder cows [1,2]. Several factors are involved as causes of repeat breeder.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of such antibiotic treatment for the management of repeat breeder cows is still controversial and results are variable. A variety of antibiotics such as cephapirin [6,7], penicillin [1], oxytetracycline [7], cephalexin, gentamycin, and enrofloxacin [8] have been infused into the uterus for improvement of pregnancy rates in repeat breeder cows. Interestingly, intrauterine infusion of antiseptic solution, 1% Lugol’s iodine has also been successfully used for management of repeat breeder cows [9].…”
Section: Introductionmentioning
confidence: 99%